The effect of intensive reading on Politeknik Sandakan Sabah students' presentation performance / Loo Sook Yee - Loo, Sook Yee (2014)
The purpose of this study was to examine the effect of intensive reading on Politeknik Sandakan Sabah students' presentation performance. This study involved 98 students from Diploma Tourism, Diploma Agro Technology and Diploma Aquaculture. The treatment and control groups consisted of 44 students and 54 students respectively. The study was conducted in Politeknik Sandakan Sabah. An intensive reading module was used to carry out the presentation practices with treatment group. These presentation practices is to test the presenting ability with the intensive reading module between the students who participate in the intensive reading module compared to those who do not participate. Oral Presentation Achievement tests (Pre-test and Post-test) with same rubrics were used as the instrument. Both groups were given the Pre-test and Post-test. Results from both tests were analyzed using an adapted 'Statistical Package for Social Science' or SPSS. On sample T-test was used to evaluate the mean gain scores between the two groups. It shows that the significant (P-value) is 0.000, smaller than 0.05. Therefore, this supported the hypothesis that students presented with intensive reading module have higher scores on presentation practices than those presented with individual learning without intensive reading supported. The Treatment Group's mean gain score shows an increase of 15.37 and the Control Group's mean gain score shows an increase of 1.03 in both tests despite the different methodologies used on them. This means, the Treatment Group students far better than the Control Group students. No doubt, intensive reading module affects Politeknik Sandakan Sabah students' presentation performance.